Torsional Oscillations Mitigation via Interval Type-2 Fuzzy Logic Brake Control (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Turbine-generator shaft torsional oscillations is an interdisciplinary power system dynamic problem because it encompasses mechanical and electrical sectors of power grids. They give rise to a premature expenditure of fatigue life of the turbine-generator shaft metal which could lead to shaft cracks. This paper introduces an interval type-2 fuzzy logic controller to regularize the dynamic braking interventions of a novel braking resistor model for mitigation of torsional oscillations resulting from unsuccessful autoreclosure procedures near generation stations. The effectiveness of proposed scheme is elucidated by considering the unsuccessful autoreclosure of three-phase-to-ground fault in a single machine infinite bus power system via MATLAB/Simulink-based modeling and simulation environment with the help of interval type-2 fuzzy logic controller toolbox. The comparative simulation results with and without the suggested mitigation regime show that the proposed scheme is effective in the mitigation of torsional torque oscillations
Keywords: Dynamic brake resistance; Interval type-2 fuzzy logic; MATLAB/Simulink; Torsional oscillations.